SIMULATION OF ACTION OF GAS CHEMICALLY ACTIVE JETS ON DESTROYED MATERIAL - Viktorov S.D.; Demchenko N.G.; Kuznetsov A.P. (My University, 2001)
Experiments in area of liquid chemically active jets on destroyed material have shown high efficiency of this process. In order to provide material saving, opportunity for the liquid jets replacement with gas jets has been investigated. In this case, interaction between frozen sand with water and gas chemically active jet has been studied. Results of the investigations have shown efficiency of action of gas chemically active jets under conditions of low stagnation pressure. The obtained results make it possible to separate phenomenon of filtration of substance from chemically active jet. The filtration is one of the main components of the process.